Kepemimpinan Pendidikan Islam: Sebuah Konsep, Tantangan, dan Strategi - Pohan, Muhammad Munawir; Saleh, Ahmad Syukri; Ritonga, Ahmad Husein (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2024)
The lack of understanding of comprehensive educational leadership can encourage in-depth discussions for educational leaders in formulating the concept of Islamic educational leadership that combines universal Islamic values with the current educational context. This research aims to explain the concept of Islamic educational leadership. The type of research used in this research is library research. The results showed that Islamic educational leadership must be able to direct and guide members of the educational community to achieve the educational goals set. Islamic education leadership must face global challenges, harmonize all parties' interests, ensure leadership competence and professionalism, and develop the ability to adapt, collaborate, and innovate. It is concluded that effective and adaptive Islamic education leadership is very important to realize the vision and mission of Islamic education in facing various challenges in the era of globalization.